The Effects of the Coating and Aging of Biodegradable Polylactic Acid Membranes on In Vitro Primary Human Retinal Pigment Epithelium Cells - Faura, Georgina; Studenovska, Hana; Sekac, David; Ellederova, Zdenka; Petrovski, Goran; Eide, Lars (Biomedicines, 2024)
Age-related macular degeneration (AMD) is the most frequent cause of blindness in developed countries. The replacement of dysfunctional human retinal pigment epithelium (hRPE) cells by the transplantation of in vitro-cultivated hRPE cells to the affected area emerges as a feasible strategy for regenerative therapy. Synthetic biomimetic membranes arise as powerful hRPE cell carriers, but as biodegradability is a requirement, it also poses a challenge due to its limited durability. hRPE cells exhibit several characteristics that putatively respond to the type of membrane carrier, and they can be used as biomarkers to evaluate and further optimize such membranes. Here, we analyze the pigmentation, transepithelial resistance, genome integrity, and maturation markers of hRPE cells plated on commercial polycarbonate (PC) versus in-house electrospun polylactide-based (PLA) membranes, both enabling separate apical/basolateral compartments. Our results show that PLA is superior to PC-based membranes for the cultivation of hRPEs, and the BEST1/RPE65 maturation markers emerge as the best biomarkers for addressing the quality of hRPE cultivated in vitro. The stability of the cultures was observed to be affected by PLA aging, which is an effect that could be partially palliated by the coating of the PLA membranes.
Keywords: AMD; DNA damage; retinal pigment epithelium; eye; nanofibrous membrane; gene expression; RPE; retina